A water-soluble and photostable aggregation-induced emission lumogen for imaging Gram-negative bacteria by supramolecular assembly. (October 2021) - Hu, Xichao; Jiang, Lirong; Ye, Huan; Zhu, Beitong; Niu, Guangle
Abstract: Detection of lipopolysaccharide (LPS) and Gram-negative bacteria is essential for bacterial diagnostics and healthcare monitoring. Herein, we designed an amphiphilic fluorescent probe (CS-PyB ) with an aggregation-induced emission (AIE) feature and high photostability for fluorescence turn-on detection of LPS. The AIE-active probe CS-PyB binds with LPS via multiple intermolecular interactions to form highly emissive aggregates, resulting in a large fluorescence enhancement. CS-PyB is highly selective for LPS over other biological analytes and exhibits a low limit of detection (LOD = 40.7 nM) toward LPS. Besides, high-contrast discrimination of Gram-negative bacteria ( E. coli ) over Gram-positive bacteria ( S. aureus ) is successfully achieved using CS-PyB . Significantly, our LPS probe also possesses superior resistance to photobleaching. These remarkable performances render the photostable LPS probe CS-PyB as a robust candidate for long-term dynamic tracking of Gram-negative bacteria associated infections and diseases. Graphical abstract: Image 1 Highlights: A fluorescent probe (CS-PyB ) with AIE feature was developed for sensitive fluorescence lighting-up detection of LPS. CS-PyB is highly selective for LPS and exhibits a low limit of detection (LOD = 40.7 nM) for LPS. CS-PyB has achieved high-contrast discrimination of E. coli over S. aureus .